Wrist pulse diagnosis of stable coronary heart disease based on acoustics waveforms. (February 2022) - Cui, Jian; Song, Lucheng
Highlights: This paper presented for the first time the stratification of pulse into five layers. In addition, for the first time, acoustic sensors were used to collect pulse acoustic waveforms in 5 layers in 3 parts of the radial artery. Time-domain analysis, frequency domain analysis and EMD analysis were used to analyze the pulse waveforms of healthy people and patients with stable coronary heart disease at various locations and levels. The results showed that the acoustic waveforms in the third and fourth layers of the left Cun pulse of patients with stable coronary heart disease was significantly different from healthy people, which provided a basis for TCM doctors to assist in the diagnosis of coronary heart disease by pulse. Abstract: Background and objective: As a common pathological pulse, unsmooth pulse has important diagnostic value in traditional Chinese medicine (TCM). In modern pulse diagnosis, unsmooth pulse plays an important role in the diagnosis of disease location and nature, but there are few studies on it. In this paper, a pulse diagnosis approach based on acoustic waveforms was proposed, the wrist pulse was divided into five layers vertically for the first time. Five layers acoustic waves of the radial artery in stable coronary heart disease (CHD) patients and relatively healthy people were compared to explore whether there are abnormal changes in acoustic pulse in stable CHD patients. Methods: The acoustic features of unsmooth pulse in patients with stable CHD were analyzed in time domain, frequency domain and empirical mode decomposition, combined with shannon entropy and multi-scale entropy. Sixteen pulse characteristics were discovered, and one-way analysis of variance were performed. The characteristics of the two groups were tested by T test. 13 features were used to identify patients with stable CHD by support vector machine (SVM). Results: Compared to healthy people, all parameters of the third layer of the stable CHD left Cun pulse were significantly different from those of the healthy people. The identification rates of the fourth and third layer of the left Cun pulse were the first (90.79%) and the second (88.16%), respectively. Conclusion: Abnormal acoustic pulse appeared in the radial artery in patients with stable CHD. According to these changes, patients with stable CHD can be effectively identified from the perspective of pulse.